Transesterification reaction of the BaSO4-filled PBT/poly(ethylene terephthalate) blend - Lee, SS; Kim, J; Park, M; Lim, S; Choe, CRM (JOHN WILEY & SONS INC, 2001)
For the poly(butylene terephthalate) (PBT)/poly(ethylene terephthalate) blend system, the addition of a barium sulfate (BaSO4) particle, the surface of which was modified with a titanate coupling agent, suppressed the transesterification reaction. The polyester chain ends, considered one of the main sites of transesterification reactions, were blocked through a chemical reaction with the surface hydroxyl groups of the BaSO4 particle; a block copolymer-like architecture was obtained with a BaSO4 linkage. The formation of the block copolymer-like structure for the polyesters stuck to the BaSO4 particle facilitated crystallization by providing a crystallization nucleus without a significant transesterification reaction, resulting in higher mechanical properties. (C) 2001 John Wiley & Sons, Inc.